KAJIAN TUGAS DAN FUNGSI POLRI DALAM PENEGAKAN HUKUM - I WAYAN JULIARTHA SUDA; I WAYAN SUWANDA (Universitas Mahasaraswati K. Mataram, 2022)
The National Police as an institution and part of the chess dynasty of law enforcement is an institution that has an important and strategic role in the law enforcement process. Through the organization and the processes that take place in it, society accepts the embodiment of legal goals. Justice, for example, is no longer an abstract concept, but is actually given to members of the community in the form of ratification of certain actions. Legal certainty is realized through judges' decisions which reject vigilante acts committed by community members. Order and security become something real through police actions organized by the Police agency.The role of legal regulations is quite large in relation to the implementation of the regulations carried out by law enforcers. In a tone that may be a bit extreme, it can be said that the success or failure of law enforcers in carrying out their duties has actually started since the legal regulations that must be implemented are made. With the increase in increasingly sophisticated technology in the field of public security and safety, Police agencies can now rely on computer-operated devices to record and examine various matters relating to public order and crime more accurately and precisely. Investigation of criminal cases and violations that have become real/factual threats (AF) is the duty and responsibility of the police to the community in the field of law enforcement. So that the investigation process carried out by the police does not violate the law and human rights, there are three important principles that must be upheld and adhered to by every police officer, namely: the principle of presumption of innocence, the right to be tried fairly and respect for the dignity and privacy of everyone